Agent-based modeling for decision making in economics under uncertainty - Ben Vermeulen; Andreas Pyka (Kiel Institute for the World Economy (IfW), 2015)
Ever since the emergence of economics as a distinct scientific discipline, policy makers have turned to economic models to guide policy interventions. If policy makers seek to enhance growth of an open capitalist economy, they have to take into account, firstly, the uncertainties, inefficiencies, and market failures faced by the agents in the economy, and, secondly, the activities, network structure, and interactions in the innovation & production system. The authors discuss ins-and-outs of developing and using (encompassing and empirically calibrated) agent-based models for (i) abductive theorizing about causes for empirical realities, and (ii) evaluating effects of policy interventions. To ensure that derived policies are suitable to intervene in the real world and not just the stylization of it, they discuss validity and operationalization of agent-based models as well as interpretation of simulation results.
Keywords: B52; C63; D81; O32; P10; 330; decision making; uncertainty; rationality; agent-based model; policy instrument; innovation economics; Schumpeter